Beware of prosthetic valve thrombosis despite therapeutic anticoagulation. Issue 3 (9th March 2007) - Foley, Paul William Xavier; Sharma, Raj; Karla, Paul R
Abstract : Patients with mechanical heart valves require anticoagulation within carefully controlled ranges to prevent valve thrombosis, a life-threatening condition. The majority of doctors will be required to manage anticoagulation, often on a temporary basis such as during elective procedures. As long-term anticoagulation management moves away from specialised hospital clinics, there needs to be widespread awareness of the complications of sub-therapeutic international normalised ratios (INRs).